Evaluating the pre-treatment protocol required to produce an effective carbonized waste adsorbent for organic pollution control - Priyanka,; Vashisht, Devika; Taylor, Martin J.; Mehta, Surinder K. (Frontiers in Environmental Science, 2023)
With the goal of fostering the circular economy, the present work was devised to minimize and manage agricultural waste by transforming it into biochar; a versatile dye removal adsorbent.Waterways across the globe are frequently fouled and contaminated with organic materials, especially via unregulated industrial effluents, producing toxic water supplies. Rhodamine B (RhB) and Methylene blue (MB) dyes were used as model organic pollutants in water. The contaminants were then readily extracted from environmental samples using sustainable wheat straw derived biochars. These materials were utilized in an effort to link the circular economy directly to environmental protection, reducing organic contamination by using a low carbon solution. Herein, two methods were adopted to refine a low temperature carbonized material, dependent on initial pre-treatment; leaching followed by milling (method-I) and milling followed by leaching (method-II). Scanning Electron Microscopy (SEM), nitrogen physisorption, proximate and ultimate analysis and Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) were used to examine the properties of the synthesized materials. It was found that by altering the process of initial waste pre-treatment, an increase in available surface area (6.284 m 2 g -1 to 20.754 m 2 g -1 ) and pore structure can be found post feedstock pyrolysis. Additionally, FTIR of the biochar post extraction supported the adsorption process of both dyes, demonstrating a change in dye-adsorbent bonding, depending on the initial waste pre-treatment for the biochar.In batch mode, several operating parameters including pH, concentration, duration, and dose were optimized. Kinetics and adsorption isotherm studies for biochar synthesized by method-II pretreatment (BC-II) revealed that the system follows Pseudo-first-order kinetics and Freundlich adsorption isotherm model with the relative R 2 of 0.9989 and 0.9880 for RhB, comparing with 0.9933 and 0.9932 for MB. The optimal produced biochar, BC-II effectively removed 91.06% of RhB from solution at pH 4 and 92.43% for MB at pH 8. This study brings forth a solution to enhance waste management by creating a circular scenario and alleviate environmental contamination by utilizing wheat straw as a biochar adsorbent, produced under controlled and low temperature conditions.